Complications of intrauterine intravascular blood transfusion: lessons learned after 1678 procedures. (August 2017) - Zwiers, C.; Lindenburg, I. T. M.; Klumper, F. J.; de Haas, M.; Oepkes, D.; Van Kamp, I. L.
ABSTRACT: Objective: Maternal alloimmunization to fetal red‐blood‐cell antigens is a major cause of fetal anemia, which can lead to hydrops and perinatal death if untreated. The cornerstone of management during pregnancy is intrauterine intravascular blood transfusion (IUT). Although this procedure is considered relatively safe, complications continue to occur. The aim of this study was to evaluate rates of procedure‐related complications and perinatal loss following IUT, and their change over time, in order to identify factors leading to improved outcome. Methods: This was a retrospective analysis of all IUTs for red‐cell alloimmunization performed at the national referral center for fetal therapy in The Netherlands, from 1988 to 2015. Differences in complication rates and their associations with alterations in transfusion technique after 2001 were assessed. Results: Between 1988 and 2015, 1678 IUTs were performed in 589 fetuses. For IUTs performed in 2001 and onwards, there was significant improvement in survival (88.6% vs 97.0%, P < 0.001) and a decline in procedure‐related complications per fetus (9.8% vs 3.3%, P = 0.001) and per procedure (3.4% vs 1.2%, P = 0.003) compared with those performed before 2001. Procedure‐related perinatal loss declined from 4.7% to 1.8% per fetus ( P = 0.053). Beneficial changes in transfusion technique were routine use of fetal paralysis, increased use of intrahepatic transfusion and avoidance of arterial puncture. Conclusions: IUT has become an increasingly safe procedure in recent years when performed by experienced hands. The chosen technique should be fine‐tuned according to the patient's individual situation. The declining complication rates are most likely related to center volume: this rare procedure is best performed in experienced fetal therapy centers. © 2016 Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of International Society of Ultrasound in Obstetrics and Gynecology.